Peningkatan Kemandirian Ekonomi Pondok Pesantren Ahmad Dahlan, Kriyan melalui Usaha Ternak Ikan Nila dan Ikan Gurami - Arie Kusuma Paksi; Krisna Silawa; Chalila Raihan Nabilazka (Jurnal Surya Masyarakat, 2023)
Enhancing entrepreneurial spirit at Pondok Pesantren (Islamic Boarding Schools) becomes a crucial point in the effort to improve the independence of the institution, considering the increasing needs and its potential to contribute to the economic well-being of the institution. In addition, the students (santri) also receive lessons in entrepreneurship, enabling them to learn about business and gain the confidence to become entrepreneurs, especially if supported by the readiness of the institution to facilitate its students. Besides the independence of the institution itself, entrepreneurship at Pondok Pesantren also benefits the surrounding community when the initiated business manages to empower the local community. Pondok Pesantren Ahmad Dahlan, located in Kriyan, Kulon Progo, Yogyakarta Special Region, is one such institution that has the potential to develop an independent business. This is considering that the institution already has a 3kg Gas (Melon) business and has received prior training. Pondok Pesantren Ahmad Dahlan has significant potential in developing entrepreneurial spirit, both among its students and administrators. This results in a lack of diversification of economic revenue sources to support the institution's activities. To address this issue, the Community Service Team from Universitas Muhammadiyah Yogyakarta (UMY) implemented a community service program focusing on the cultivation of tilapia and gourami fish. The methods used include training, field practice, and ongoing assistance, monitored and evaluated periodically. The findings indicate a significant increase in knowledge and skills in fish cultivation among students and administrators, as well as the potential for a significant increase in income from this fish farming business. Thus, this program positively contributes to the utilization of land and human resources for additional income to support the activities of Pondok Pesantren Ahmad Dahlan.